Questions of formation of musical culture of the person during reading the notes from a sheet - O.M. Yaroshenko (Academy of Cognitive and Natural Sciences, 2006)
The article considers the general provisions and components of receptions of reading of the notes from a sheet, methodical receptions offormation of skill and training of high-speed reactions an musical marks and musical culture of the person.